THE EVOLUTION OF ROMANIA’S GROSS DOMESTIC PRODUCT IN THE LAST TEN YEARS - Constantin ANGHELACHE (Revista Română de Statistică, 2012)
This paper proposes a complex analysis of the GDP’s evolution inour country. Given the position of the indicator in the context of the national economy, such analysis is much more important, knowing that the results outline the performances of all activities within the economy.